Integrating molecular biomarkers in breast cancer rehabilitation. What is the current evidence? A systematic review of randomized controlled trials - Invernizzi, Marco; Lippi, Lorenzo; Folli, Arianna; Turco, Alessio; Zattoni, Lorenzo; Maconi, Antonio; de Sire, Alessandro; Fusco, Nicola (Frontiers in Molecular Biosciences, 2022)
Background. Quality of life issues are a crucial burden in breast cancer (BC) survivors with relevant implications in terms of survivorship and sanitary costs. The increasing long-term survival of these patients provides new challenges, with translational research now focusing on innovative and tailored approaches to improve their complex management. In this scenario, several emerging biomarkers have the potential to improve the clinical rehabilitative management of patients with BC. However, to date, guidelines supporting biomarkers implementation in this area are still lacking. Therefore, the aim of this systematic review was to summarize the currently available biomarkers that might be potentially integrated into rehabilitation practice to promote a precision medicine approach to BC survivorship issues. Methods. On March 9th, 2022, PubMed, Scopus, Web of Science, Cochrane, and PEDro were systematically searched for randomized controlled trials (RCTs) assessing rehabilitation interventions in BC patients. Molecular biomarkers modifications induced by physical exercise have been assessed through the review of the study protocols and published results. The Jadad scale was used to assess the quality of the studies included. Results. Out of 2,224 records, 22 studies were included in the present systematic review. Exercise therapy showed significant results in 15 RCTs, in terms of metabolic biomarkers, including glycemic and insulin profile, and lipid profile (p≤0.05). Similarly, 12 papers underlined significant effects in inflammation and immune response biomarkers, including TNF-α, IL-6, IL-10, C-reactive protein, leptin, and adiponectin (p≤0.05). On the other hand, cardiac biomarkers were assessed in 3 papers without reporting significant differences after exercise therapy (p=NS). The quality assessment identified 19 RCTs as high-quality studies and 3 RCTs of low quality. Conclusions. Our findings reveal significant biochemical perturbations in key molecules induced by physical exercise in patients with BC, suggesting room for the implementation of actionable biomarkers. Future research might clarify the role of biomarkers on treatment effectiveness monitoring, to optimize rehabilitative strategies tailored to patient’s needs.